Listening Difficulties and Strategies in Preparing for IELTS Listening Test Using Online Learning: A Case Study of Intensive English Learners - Lieyana Teo Mohd Zulkifli Teo; Nurul Imtiaz Abd Gani; Muhammad Hafiz Ummah (Universitas Teknokrat Indonesia, 2022)
AbstractListening is one of the significant roles in the educational process of English language learning. Despite its importance in our daily communication, it is a skill where most EFL learners struggle with during online listening comprehension practice. This study examines the listening difficulties faced by the EFL learners (i.e., Intensive English learners) in preparing for the IELTS listening test. In this paper, the researchers reviewed the terms listening and online learning, including their significance, process of listening comprehension, learners’ difficulties based on the content of the listening text, failure to concentrate, listener, speaker, and environment, as well as strategies to overcome the issue. The participants were 16 international learners undertaking an Intensive English Course in Universiti Utara Malaysia (UUM). A questionnaire was employed to elicit the participants’ listening difficulties and strategies used in the Intensive English classes. The data were analysed and reported using the descriptive quantitative method (mean value, standard deviation, and percentage). The results of this study on learners’ difficulties and the strategies to overcome the problems in listening in the intensive English classes are also discussed. Findings on understanding learners’ issues would enable the English instructors to help learners develop effective learning strategies and improve their listening comprehension abilities. Keywords: IELTS Listening Test, Intensive English Learners, Listening Difficulties, Listening Strategies, Online Learning